Studies on time series properties of forward discount in foreign exchange market / Aidil Rizal Shahrin - Aidil Rizal, Shahrin (2015)

(untitled)
Recent literature has suggested that one explanation of the forward bias puzzle is the validity of econometric inference in testing the forward rate unbiasedness hypothesis (FRUH), which results in biased or size distortion. This is due to the highly persistent behaviour of the forward discount. Two models of time series with a highly persistent process are quite successful in explaining the puzzle; long memory and root near unity. However, Choi and Zivot (2007), who focus on long memory, and Sakoulis et al. (2010), who focus on the autoregressive (